Study of some parameters of humoral immunity in asthmatic elderly patients - Marisela Pérez Pacareu; Alina González Paredes; Rafael Zamora Puerta; Dayamí García Torres (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Aging process affects the whole body, including the respiratory and immune systems. Reductions of immunoglobulin secretion, together with environmental factors, increases susceptibility of elderly people to a more severe type of asthma. One of the effective ways of evaluating their immune system is the study of humoral immunity through immunoglobulin quantification. Objective: To analyse the characteristics of immunoglobulin G, A and M quantification in a sample of elderly patients. Methods: Descriptive study of two case series: a group of 60 years-old asthmatic patients and a group of patients younger than 60 years. All of them were received in Cienfuegos Allergy External Consultation, during one year and quantities of immunoglobulin G, A and M were measured. Results: There was higher incidence in female patients and patients between 60 and 79 years. We confirmed irregularities in immunoglobulin G quantification, not in IgA and IgM. Conclusions: Knowledge about humoral immunity in asthmatic elderly patients allows being more careful in their treatment.